2011
DOI: 10.1093/ecam/neq003
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Atherogenic Activity of Ethanolic Fraction of Terminalia arjuna Bark on Hypercholesterolemic Rabbits

Abstract: Atherosclerosis which results from gradual deposition of lipids in medium and large arteries is a leading cause of mortality worldwide. Terminalia arjuna is a herb of Combretaceae family which contains hypolipidemic compounds and flavonoids with high antioxidative properties. This study was conducted to determine the effect of ethanolic fraction of T. arjuna on blood lipids and atherosclerosis in rabbits fed with high fat diet (HFD). Twenty New Zealand rabbits of either sex were randomly divided into five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…This effect leads to a decrease in TCh, LDL-c and TG levels in serum of CA-treated group of rats. Consequently, it showed a reduction of body weight as antiobesity action (Subramaniam et al 2011). In previous studies, the chronic increases in circulating leptin caused sustained increases in arterial pressure and heart rate and was consistent with a possible role for leptin in obesity hypertension (Shek et al 1998;Kohlstedt et al 2009 ) demonstrated that; it also could increase heart rate by increasing cardiac The sonography also revealed that HFD might contribute to hepatic steatosis, compared to Fluv and CA groups, and clearly appeared in Fig.…”
Section: Discussionsupporting
confidence: 79%
“…This effect leads to a decrease in TCh, LDL-c and TG levels in serum of CA-treated group of rats. Consequently, it showed a reduction of body weight as antiobesity action (Subramaniam et al 2011). In previous studies, the chronic increases in circulating leptin caused sustained increases in arterial pressure and heart rate and was consistent with a possible role for leptin in obesity hypertension (Shek et al 1998;Kohlstedt et al 2009 ) demonstrated that; it also could increase heart rate by increasing cardiac The sonography also revealed that HFD might contribute to hepatic steatosis, compared to Fluv and CA groups, and clearly appeared in Fig.…”
Section: Discussionsupporting
confidence: 79%
“…These were divided into different groups on the base of different treatments. Ultimately, the rabbits that were given an ethanolic extract of this plant shown more valuable results like reduction of atherosclerosis and some other cardiac problems (Subramaniam et al, 2011).…”
Section: Terminalia Arjunamentioning
confidence: 99%
“…The bark of the plant is used as anti-ischemic and cardioprotective (Bone and Morgan, 1996). T. arjuna bark extract has been found to be beneficial for heart failure, coronary artery disease, and high cholesterol levels coronary arterial disease (Subramaniam et al, 2011;Kapoor, 2001). It has been found to significantly increase the activity of lipoprotein lipase as well as plasma lecithin-cholesterol acyltransferase mediated hepatic bile acid synthesis and reduces the activity of lipogenic enzymes including 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCoA) reductase, glucose-6-phosphate dehydrogenase and malate dehydrogenase (Patil et al, 2011).…”
Section: Introductionmentioning
confidence: 99%